Vida de professor: o pessoal e o profissional na construção da trajetória docente - Silveira, Juliana da Silva (2014)
This study is entered on line Research Training, Knowledge and Professional Development Program Graduate Education, PPGE/CE/UFSM at Masters level. The goal is to provide an approach to life story of a Physical Education teacher active in the Master's degree in Physical Education at the Center for Sports and Physical Education ( CEFD / UFSM ) . In the specific goals were scored in the life of the teacher's family, school life, the choice of teaching as a profession, the initial training course, entrance into the classroom as a teacher to continuing education and the construction of pedagogical approach to classes Physical education Critical Theory grounded in Emancipation. The methodology used is a qualitative one second Bauer, Gaskell and Allum (2003). The method used is the biographical - life story and the procedure for the collection of information will be the narrative interview. Through autobiographical narrative better understand the factors that led them to choose the profession teacher, how is the constitution of the training course teacher, as was the entry into the teaching and situations of family life that interfered in these events during life. For the analysis of the information obtained will use thematic analysis. Family life in childhood was marked by freedom, enrollment in school was in boarding school system. Presented to the boarding begins Athletics and interest in Physical Education. He graduated in Physical Education, is specialization, master and gets the first doctoral scholarship in Germany in Physical Education through the Goethe Institut. History of beautiful and exciting life permeated by the construction of professional development and sustained periods of estrangement from family.